Country Roads: Travel, Visibility, and Late Classic Settlement in the Southern Maya Mountains. (17th February 2019) - Carter, Nicholas; Santini, Lauren; Barnes, Adam; Opitz, Rachel; White, Devin; Safi, Kristin; Davenport, Bryce; Brown, Clifford; Witschey, Walter
ABSTRACT: Mayanist archaeology has long been concerned with creating and evaluating explanatory models for the locations of ancient sites relative to one another and to the physical geography of the Maya world. This study combines epigraphic data and spatial analyses to explore motivations for settlement location and to interrogate territorial strategies in Late Classic (a.d. 600–830) kingdoms in the southern Maya Mountains, around the modern towns of Dolores and Poptún, Guatemala. Least-cost path analyses were used to model natural travel corridors and their relationship with site location was assessed. In conjunction, viewshed analyses were applied to evaluate the importance of visual connections to likely travel routes. The results are considered in the context of the socio-politics and economics of the region, and raise questions about the character of and interconnections between travel, exchange, settlement location, and mechanisms for reinforcing territorial claims in the Late Classic Southern Maya Mountains.